Reconstitution of maltose chemotaxis in Escherichia coli by addition of maltose-binding protein to calcium-treated cells of maltose regulon mutants. - Brass, J M (1984)
Maltose chemotaxis was reconstituted in delta malE cells lacking maltose-binding protein (MBP). Purified MBP was introduced into intact cells during incubation with 250 mM CaCl2 in Tris-hydrochloride buffer at 0 degrees C. After removal of extracellular CaCl2 and MBP, chemotaxis was measured with tethered bacteria in a flow chamber or with free-swimming cells in a capillary assay. About 20% of tethered cells responded to 10(-4) M maltose; the mean response times were about half those of CaCl2-treated wild-type cells (100 s as opposed to 190 s). In capillary tests, the maltose response of reconstituted cells was between 15 and 40% of the aspartate response, about the same percentage as in wild-type cells. The best reconstitution was seen with 0.5 to 1 mM MBP in the reconstitution mixture, which is similar to the periplasmic MBP concentration estimated for maltose-induced wild-type cells. Strains containing large deletions of the malB region and malT mutants lacking the positive regulator gene of the mal regulon also could be reconstituted for maltose chemotaxis, showing that no product of the mal regulon other than MBP is essential for maltose chemotaxis.